Die Vignette als Übung der Wahrnehmung / The vignette as an exercise in perception Zur Professionalisierung pädagogischen Handelns / On the professionalisation of educational practices - Agostini, Evi; Peterlini, Hans Karl; Donlic, Jasmin; Kumpusch, Verena; Lehner, Daniela; Sandner, Isabella (Verlag Barbara Budrich, 2023)
Pedagogical work requires the willingness to engage with new situations and with people in their diversity. This book does not offer any simple recipes, but a gentle approach to important steps towards professionalisation in the teaching profession. These lead via an open attitude of perception and the inclusion of corporeality to an insight into how learning and teaching processes can be understood in a new or different way. With vignettes and examples from different pedagogical fields, the theoretical concepts are presented and reflected on their application. The book contains a German-language and an English-language version.